The clinical significance of T-cell regulation in hypertension treatment - Fu, Miaoxin; Lv, Mingzhu; Guo, Jinyue; Mei, Aihua; Qian, Hang; Yang, Handong; Wu, Wenwen; Liu, Zhixin; Zhong, Jixin; Wei, Ying; Min, Xinwen; Wu, Haiyan; et al. (Frontiers in Immunology, 2025)
Hypertension, a globally prevalent condition, is closely associated with T cell-mediated inflammatory responses. Studies have shown that T cells, by secreting pro-inflammatory cytokines such as interferon-gamma (IFN-γ), Interleukin-17 (IL-17), and Tumor necrosis factor-alpha (TNF-α), directly lead to vascular dysfunction and elevated blood pressure. The activation of Th1 and Th17 cell subsets, along with the dysfunction of regulatory T cells (Tregs), is a critical mechanism in the onset and progression of hypertension. This review explores the role of T cells in the pathophysiology of hypertension and discusses potential therapeutic strategies targeting T cell regulation, such as immunotherapy and gene-editing technologies. These emerging treatments hold promise for providing personalized therapeutic options for hypertensive patients, reducing inflammatory complications, and improving treatment outcomes.